Investigations of ice and emitter properties from radio signals recorded with ARIANNA - Lahmann, Robert (Proceedings of Science, 2019)
ARIANNA is an in-ice radio detector for neutrinos in the energy range from 1016 eV to 1020 eV which is currently in its pilot-phase in Antarctica. It exploits the so-called Askaryan effect by which radio signals are emitted from neutrino-induced particle showers in ice. Geometric optics is an efficient tool to study the propagation of electromagnetic signals through a medium such as ice, using ray tracing to predict the response induced in an antenna for a given arrangement of emitter and receiver within the medium. Analyzing and understanding the antenna response to calibration signals under well-defined conditions is important to develop reconstruction algorithms of neutrino properties, most notably the interaction vertex and energy, and to understand and characterize the properties of the ice. Recent results obtained with the data collected during the 2018-2019 Antarctic season will be presented.
CRIS-Team Scopus Importer:2021-04-20